Fishing Gear Used for River Lamprey Lampetra fluviatilis (L.) Catches: Documenting Rivers that Flow into the Baltic Sea. Part I, Sweden - Sjöberg, Kjell (Umeå University Library, 2014)
The river lamprey (Lampetra fluviatilis (L.)) is an anadromous fish that has a growth phase in the sea, then migrates up rivers mainly during autumn for spawning next spring. It is during this spawning migration the lampreys are caught in rivers. Lamprey fishing has been documented in the Baltic Sea region at least since the fifteenth century, and some of the fishing gear used has remained largely unchanged for hundreds of years. In recent decades however, new material has replaced wood, although the design of the gear is still often the same as before. In this study lamprey rivers in Sweden, Finland, Latvia and Estonia were visited and the lamprey fishing gear was documented. There are differences in the use of fishing gear both within countries and among countries as regards gear type and the ways in which the fishermen use different fishing techniques to suit the conditions found in various rivers.